Salute in Italia: ancora un diritto per tutti? Un confronto col sistema sanitario cubano (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Italy is the world’s eighth-largest country by nominal GDP, despite the high rate of youth unemployment and the growing number of people living in absolute poverty. According to Bloomberg, Italy still stands out in fourth place in the world for the quality of its National Health System, that was created as public funded, free and universal. Nevertheless, the Covid-19 pandemic has led to the immediate deflagration of the healthcare system. According to ISTAT, 10% of Italians has given up to be treated in the last year, while in the same period 32.8 million people have had necessary medical treatments cancelled or postponed. The profound contradictions behind the inequalities and social suffering in our country are the result of neoliberal policies that negatively affect our individual and collective health status, due to economic and material factors, as well as due an inexorable process of dismantling of the National Health System. The purpose of this article is to show the profound transformations that characterize the Italian healthcare system, in comparison with the Cuban healthcare model, a country where, despite the economic differences from the G8 countries, has been unanimously recognized as being in the vanguard for the quality of the healthcare and its ability to manage the Covid-19 pandemic.
Keywords: Global health; healthcare system; Italy; Cuba; primary health care